Boyden chamber-based method for characterizing the distribution of adhesions and cytoskeletal structure in HT1080 fibrosarcoma cells - Tóvári, József (Cell Adh Migr, 2014)
A 2D model was previously presented that describes the gliding motility of human fibrosarcoma cells. The model was based on the observation that adhesions are present only on the outer rim of the leading lamella of the semicircular cell. The present model describes the organization of adhesions and the cytoskeleton of migrating HT1080 fibrosarcoma and LX2 hepatic stellate cells in three dimensions. The migration assays were performed in a modified Boyden chamber using fibronectin, Matrigel, or collagen I as chemoattractants. The distribution of the adhesions was analyzed by confocal laser scanning microscope, and following decoration with heavy meromyosin, the organization of actin filaments was analyzed by electron microscopy. Double labeling was performed to study the relationship of the actin and vimentin filament network in the moving cells. Vinculin containing adhesions were observed only at the front of the cell in the form of a ring while passing through a filter pore of the Boyden chamber. Actin filaments were present only below the plasma membrane, except the very tip of the leading lamella. Vimentin intermediate filaments were localized around the cell nucleus behind the actin filament-rich lamella. This paper describes a model of the organization of adhesions and the cytoskeleton of migrating cells in the Boyden chamber. The model is based on the observation that adhesions are present only at the leading edge of the cell. The results extend the earlier 2D model of cell locomotion into 3D.